en - W. Sri Kusumawardani; Anak Agung Putu Putra (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2021)
This research aimed to find out the textual metafunction in the text of the state speech inauguration of the President Joko Widodo. Textual metafunction is realized by a thematization system in the form of elements of themes and rheme. Textual metafunction realized by the thematization system is related to grammatical elements used to express information in a clause. This research applied a descriptive qualitative approach. The data source of this research was in the form of an oral source from the video of President Joko Widodo's inauguration speech for two periods, namely 2014-2019 and 2019--2024 which was downloaded through the site www.youtube.com. This type of research data was written data. Written data was obtained from the results of oral transcription into written form so that data forms were obtained, such as words, phrases, groups of phrases, clauses, and text units. The theory used is the Systemic Functional Linguistics (SFL) theory proposed by Halliday and Matthiessen (2014). The method and techniques of collecting data applied in this research were the listening method and the note taking technique. Then, method and techniques of analysing data applied were the distribution method and basic techniques for direct elements. In addition, the method of presenting the results of data analysis applied was a formal method in the form of signs and symbols as well as an informal method in the form of words, phrases, phrases, clauses, and texts. The results showed that both of the themes of the text of the inauguration speech President Joko Widodo was concerning the sovereignty of the people and the Unitary Republic of Indonesia. Textual metafunction was examined based on a thematization system in the form of theme elements (topical, interpersonal, textual) and rheme. Based on the analysis, there was an increase in the use of themes from 2014 (42.2%) to 2019 (57.8%). Meanwhile, the use of rheme in 2014 was dominated by the material processing rheme, which is 27 uses, while in 2019 it was dominated by the behaviour processing rheme, which was 40 usage.